Nebulized Pentamidine-Induced Acute Renal Allograft Dysfunction - Siddhesh Prabhavalkar; Agnes Masengu; Declan O'Rourke; Joanne Shields; Aisling Courtney (Case Reports in Transplantation)
Acute kidney injury (AKI) is a recognised complication of intravenous pentamidine therapy. A direct nephrotoxic effect leading to acute tubular necrosis has been postulated. We report a case of severe renal allograft dysfunction due to nebulised pentamidine. The patient presented with repeated episodes of AKI without obvious cause and acute tubular necrosis only on renal histology. Nebulised pentamidine was used monthly as prophylaxis for Pneumocystis jirovecii pneumonia, and administration preceded the creatinine rise on each occasion. Graft function stabilised following discontinuation of the drug. This is the first report of nebulized pentamidine-induced reversible nephrotoxicity in a kidney allograft. This diagnosis should be considered in a case of unexplained acute renal allograft dysfunction.